Toxicity evalautions of ethanolic extract of Christia vespertilionis (L. F.) Bakh. F. in male sprague dawley rats - Ahmad Sayuti, Nurul Syahirah (2018)
The term Butterfly tea refers to the decoction of Christia vespertilionis (L.f.) Bakh. f. leaves which is widely consumed by cancer patients throughout Malaysia, and it has gained a huge popularity among researchers yearning to discover the real potential of this plant. Herein, this study is aimed at evaluating possible toxicity in a 14-day acute, 28-day subacute and 90-day subchronic oral toxicity of the ethanolic extract Christia vespertilionis (L.f.) Bakh. f. in male Sprague Dawley rats. The 14-day acute toxicity study was conducted to detect lethal dose 50 (LD50) Christia vespertilionis (L.f.) Bakh. f. while the 28-day subacute and 90-day subchronic toxicity studies are to detect the non-observed-adverse-effect level (NOAEL). In the acute toxicity study, rats were divided into control, 5% DMSO (vehicle) and 2000 mg/kg groups. The extract was administered orally on day 1 and observed for 14 days. Meanwhile, in the subacute and subchronic toxicity studies, a total of 30 rats were divided into control, 5% DMSO (vehicle), low dose (75 mg/kg), medium dose (125 mg/kg) and high dose (250 mg/kg) groups. The extract was administered daily from day 1 until day 28 for subacute and day 90 for subchronic. Standard toxicology parameters including mortality, behavioural changes, motor-neuronal abnormalities, feed-water consumption pattern and body weight were measured. The haematological, serum biochemical parameters and histopathological assessment of kidney and liver functions were also carried out. Results of acute oral toxicity showed that single dose (2000 mg/kg) of ethanol extract of Christia vespertilionis (L.f.) Bakh. f. leaves induced no treatment-related signs of toxicity or mortality in male Sprague Dawley rats. The haematological results also showed no changes in the control and treated groups in all 3 studies. However, serum biochemistry results for acute study, showed a significant decrease in the CK and AST level when compared with the control and treated groups. Meanwhile results for serum biochemistry in subacute and subchronic showed no changes in the control and treated groups for both studies. Organs to body weights ratio after euthanisation in all 3 studies showed no significant differences when comparing treated and control groups. On histopathological analysis, acute study showed significant differences (p<0.05) of lesions observed on hepatic necrosis (mild to moderate) and degeneration (very mild) in the treated group (2000 mg/kg). Meanwhile, subacute study showed significant differences (p<0.05) of lesions observed on high dose, medium dose and low dose groups has mild to moderate, mild and very mild lesion of hepatic necrosis and very mild hepatic degeneration and hepatitis were scored in all three groups in subacute study. Besides, for subchronic study showed significantly differences (p<0.05) in hepatic necrosis and activated kupffer cells. Hepatic necrosis was observed mild to moderate in both high dose and medium dose groups, while low dose group only had mild lesion in subchronic study. On the other hand, the number of activated kuffer cells was significantly (p<0.05) higher in low and medium dose groups compared to the high dose group. On the other hand, all three studies, there were no significant (p>0.05) on lesion for renal toxicity were scored. In conclusion, for the acute toxicity result, lethal dose 50 (LD50) of Christia vespertilionis (L.f.) Bakh. f. is greater than 2000 mg/kg and both subacute and subchronic study showed induces dose-dependent oral hepatotoxicity in rats. As hepatic necrosis was predominantly seen compared to hepatic necrosis and hepatic degeneration in subacute toxicity study, it is suggested that subchronic toxicity study of Christia vespertilionis (L.f.) Bakh. f. extract induces more permanent damage to the hepatocytes.